A content analysis on the challenges experienced in implementing technology in physical education in Indonesia - Zulkifli; Henjilito, Raffly; Makorohim, M. Fransazeli; Yani, Ahmad; Alficandra (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background: The lack of studies that specifically examines the challenges of implementing technology in physical education, with a content analysis approach using NVivo 12 Plus prompted this study to be carried out. Research Objective: This study identifies strategies to overcome these obstacles and provides recommendations for policymakers and educators. The aim is to increase the effectiveness of the learning process through more effective use of technology. This research is also encouraged because the related findings are one of the few studies that have been conducted, especially in Indonesia, so this can fill the research gap. Methods: This method combines qualitative research with content analysis. It used Nvivo 12 Plus software to discover and analyse the main themes. The units of analysis used are text search queries and case classification. Finding/Results: The findings of this study reveal that the employment of technological aids in physical education is beneficial as it allows greater access and flexibility in learning, enhances students’ motivation and participation, and offers innovative teaching-learning tools. Nonetheless, inside the Indonesian education sector, there are still identified issues regarding constrained access to technology in many places, considering gaps in the deployment of digital infrastructure and the development of students’ and educators’ digital skills. Conclusion: Improvements in telecommunications infrastructure, better digital literacy among the teaching and student populations, and opportunities for closer governmental cooperation with industry will be vital to addressing these hurdles more effectively. Although there are still some struggles, this research highlights how technology should be implemented in physical education in the digital age. This study helps identify and analyse the main challenges to developing strategies for improving technology use in physical education, especially among students and educators.